Environmental Risk in Nepal: A General Assessment - Gautam, Dilli Raj (Tribhuvan University Journal, 2010)
Not available. Key words: Environmental Risk; General Assessment Tribhuvan University Journal Volume XVI, 1993 Page: 87-93 Uploaded date: 4 October, 2010